The Primitive Path. For a Polyphony of Cognitive and Material Agencies - Giampieri, Gabriele (E|C, 2023)
Over the last quarter of century, several scientific disciplines from different perspectives have been focusing on the engagement between organisms and environment and on how cognitive and material agencies affect each other. The integration and the simultaneities of the agencies looks developing strictly from a theoretical point of view, however as analysis of interactions comes into play we – as analysts – seem doomed to preserve a dualistic perspective (cognitive VS material) while presenting our accounts and practical examples. The paper seeks to demonstrate how a pre-logic mentality might overcome the divisive cultural logics of the analysts and support instead the emergence of a polyphony of agencies occurring simultaneously during the analysis, leading towards a non-dualistic and a-chronic account of the human-material engagement.